KEARIFAN LOKAL KEPUNGAN SIALANG MASYARAKAT DESA RANTAU BARU KECAMATAN PANGKALAN KERINCI KABUPATEN PELALAWAN - Desti Zarli Mandari; Akhwan Binawan (Pelantar Press, 2025)
Kepungan Sialang is a forest area containing one or more sialang tree species. The existence of sialang trees and forest bees A. dorsata is closely related to the condition of forest cover and the type of flowering plants found around the beehive. This study aims to explain the meaning and characteristics of sialang trees and the types of sialang trees which are one of the local wisdom of the Rantau Baru Village community. This research was conducted in September 2021 in Rantau Baru Village, Pangkalan Kerinci District, Pelalawan Regency. The methods used in this research are field observations, interviews with traditional leaders of Rantau Baru Village and literature studies. The results obtained from this study are that sialang trees have characteristics, that generally having a tall trunk even reaching 40 m, wide and open crowns, sympodial branching and small to medium leaves. There are only two types of sialang trees found in Rantau Baru Village, namely Rengas Tree (Gluta renghas Linn) from the Anacardiaceae family and Cubadak Air (Parartocarpus triandus) from the Moraceae family. There are nine trees species that make up Kepungan Sialang in Rantau Baru Village including Sterculia gilva Mig., Pentace triptera Mast., Palaquium spp., Barringtonia spicata Bl., Cratoxylum arborescens, Flacourtia rukam, Pangium edule, Dillenia indica and Dysoxylum alliaceum (Blume). The Menumbai or honey harvesting process consists of the initial survey, preparation and implementation of the Menumbai process which involves the upper jagan or juragan as the harvester and the lower jagan as the honey catcher below. As one of the efforts to maintain the wisdom of Kepungan Sialang, Riau Malay Customary Institution (LAMR) of Pelalawan Regency has issued a Fatwa regarding the prohibition of cutting down sialang trees and its sanctions.